Robust Fractional Order PI Controller Tuning Based on Bode's Ideal Transfer Function. Issue 9 (2016) - Azarmi, Roohallah; Tavakoli-Kakhki, Mahsan; Sedigh, Ali Khaki; Fatehi, Alireza
Abstract: This paper presents a simple analytical method for tuning the parameters of fractional order PI (FOPI) controllers based on Bode's ideal transfer function. The proposed technique is applicable to stable plants describable by a fractional order counterpart of first order transfer function without time delay. Tuning rules are given in order to improve the robustness of the compensated system in the presence of gain uncertainty in the plant model. Finally, the designed FOPI controller is implemented on a laboratory scale twin rotor helicopter and comparison results are provided to show the effectiveness of the proposed tuning rules.